French Voices Against Colonial Legal Abuses in Algeria: Émile Larcher (1869–1918) Between Reformist Aspirations and the Perpetuation of Colonial Domination - Guebaili , Abdelhafid (The Algerian Historical Journal, 2026)
This article explores the views of the French jurist Émile Larcher (1869–1918) on the legal abuses that characterized French colonial rule in nineteenth-century Algeria, focusing on his critique of the exceptional penal system imposed on Muslim subjects. It argues that colonial law functioned less as a framework of justice and more as a mechanism of domination, legitimized by the rhetoric of reform and civilization. Within this context, Larcher emerged as a rare legal voice denouncing the arbitrary powers of the Governor-General, military commanders, and administrative officers, and criticizing institutions such as the War Councils and Disciplinary Commissions for violating the principles of justice. The study concludes that Larcher’s thought reveals the deep contradiction between France’s reformist discourse and its colonial practices. His call for the equal application of justice represented a bold intellectual effort to restore the legitimacy of law in a colonial order built on exception, defending the very legal values that colonialism had distorted in its own name.